Synthesis of the Literature: Variables Influencing Caregiver Use or Nonuse of Supportive Services - Kristina M. Childers MSN, APRN, FNP-BC (SAGE Publishing, 2019)
Two out of three caregivers (CGs) of persons with dementia (PWD) living in the community do not use supportive services or resources, and three out of four underutilize available support. These findings are troubling because CGs report many unmet needs in providing support to PWD. What predisposing, enabling, and need variables influence CGs to use or not use support services are poorly understood. This article reviews the literature on CG of PWD to find characteristic variables that are related to CG's decisions to use or not use support services. Instruments used in research studies were named to determine recommendations for future studies. The article organizes the variables following Anderson's model of predisposing, enabling, and need characteristics. It also supports future research to examine CG use or nonuse of resources that could inform practice, funding of programs, and policy.